Laboratory investigation on damping characteristics of homogeneous and stratified soil-ash system - Ram, Amit Kumar; Mohanty, Supriya (Chinese Academy of Sciences, 2023)
In this study, the damping responses of uniform soil, equi-proportional fly ash, and local soil as a single unit were investigated. The large-strain cyclic triaxial tests were performed for the specimen compacted at the desired density (95%–99% of maximum dry density). The compacted specimens were tested under the loading frequency of 0.3–1 Hz with medium confinement of 70–100 kPa. Also, the unsymmetrical behavior of the hysteresis loop was analyzed using three different damping estimation approaches, i.e. symmetric hysteresis loop (SHL), asymmetric hysteresis loop (ASHL), and the modified American Society for Testing and Materials (ASTM) method. The outcome of the study shows for fly ash, local soil, and layered soil-ash, the ASHL technique has the highest damping value, followed by ASTM and then the SHL approach. The specimens prepared under high density and subjected to high confinement show low damping values. However, the specimens tested at high frequency exhibits high damping behavior. Similarly, the damping value of fly ash determined using the SHL and ASHL methods has a similar profile and reaches a maximum at 1% shear strain value before decreasing. The composite stratified deposit exhibits more dependency on relative compaction, confining pressure, and less on loading frequency. Based on the results, it is highly recommended to use the ASHL approach, especially under large strain conditions irrespective of soil type. The maximum damping ratio of stratified deposits is always in between the damping ratio of local soil and fly ash. The damping ratio of stratified soil and local soil is slightly larger than that of the other soils, although the damping ratio of fly ash is equivalent to that of the sand and clayey soil. These results may be helpful in the accurate determination of the damping properties of the layered soil-ash system that is required in the seismic response analysis.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Asymmetric hysteresis loop; Cyclic triaxial test; Damping behavior; Homogeneous soil; Model fitting; Stratified soil-ash system; cyclic loading; estimation method; frequency analysis